1981
DOI: 10.1007/bf02370046
|View full text |Cite
|
Sign up to set email alerts
|

Utility of some nitrogen-fixing microorganisms in the phyllosphere of crop plants

Abstract: The utility of spraying some known N2-fixing microorganisms on rice leaves grown both in N-less sand culture and under field conditions was examined. The effect was compared with that of spraying a phyllosphere Nz-fixing isolate of Klebsiella, KUPBR 2, and application of nitrogenous fertilizers. All the growth parameters studied including dry weight and N-content were enhanced. Under field conditions number of tillers was increased by 26')/0 with Klebsiella pneumoniae M 5al and by 65')~, with Aphanothece. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
1
4
2
Order By: Relevance
“…The bacterial diversity associated with rhizosphere of wheat as observed in this study was significantly higher as compared to the previous reports (Guemouri-Athmani et al Requena et al 1997;Pedersen et al 1978). Streptomyces venezualae, one of the actinomycetes isolated in the present study was also a reported nitrogen fixer (Nandi and Sen 1981). Interestingly, the symbiotic nitrogen fixers such as Ensifer sp.…”
Section: Resultscontrasting
confidence: 67%
“…The bacterial diversity associated with rhizosphere of wheat as observed in this study was significantly higher as compared to the previous reports (Guemouri-Athmani et al Requena et al 1997;Pedersen et al 1978). Streptomyces venezualae, one of the actinomycetes isolated in the present study was also a reported nitrogen fixer (Nandi and Sen 1981). Interestingly, the symbiotic nitrogen fixers such as Ensifer sp.…”
Section: Resultscontrasting
confidence: 67%
“…Bacteria contribute significantly to pathogenic control, N 2 fixation, nutrient cycling, and decomposition in phyllosohere ecosystems (Ruinen, 1956;Nandi and Sen, 1981;Berg et al, 2005;Compant et al, 2005). Any effects of fungicides on microbial communities may have subsequent impacts on high trophic levels.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of a selective medium and selective growth conditions probably account for the appearance of only a single report for the isolation of Xanthobacter species from plant roots. Nandi and Sen (1981) reported that rice yield was doubled when Mycobacterium flavum (now Xanthobacter flavus) was sprayed onto rice leaves. In an ~SN study of soil diazotrophs, rice plants, grown in sterile soil amended with lactose, received 18% of the N 2 fixed by Xanthobacter flavus (Kalininskaya et al, 1989).…”
Section: Introductionmentioning
confidence: 99%